Prefrontal lesions disrupt oscillatory signatures of spatiotemporal integration in working memory. (May 2021) - Parto Dezfouli, Mohsen; Davoudi, Saeideh; Knight, Robert T.; Daliri, Mohammad Reza; Johnson, Elizabeth L.
Abstract: How does the human brain integrate spatial and temporal information into unified mnemonic representations? Building on classic theories of feature binding, we first define the oscillatory signatures of integrating 'where' and 'when' information in working memory (WM) and then investigate the role of prefrontal cortex (PFC) in spatiotemporal integration. Fourteen individuals with lateral PFC damage and 20 healthy controls completed a visuospatial WM task while electroencephalography (EEG) was recorded. On each trial, two shapes were presented sequentially in a top/bottom spatial orientation. We defined EEG signatures of spatiotemporal integration by comparing the maintenance of two possible where-when configurations: the first shape presented on top and the reverse. Frontal delta-theta (δθ; 2–7 Hz) activity, frontal-posterior δθ functional connectivity, lateral posterior event-related potentials, and mesial posterior alpha phase-to-gamma amplitude coupling dissociated the two configurations in controls. WM performance and frontal and mesial posterior signatures of spatiotemporal integration were diminished in PFC lesion patients, whereas lateral posterior signatures were intact. These findings reveal both PFC-dependent and independent substrates of spatiotemporal integration and link optimal performance to PFC.